AN IMPROVEMENT OF GRAPHITE ROD ELECTRODE OF USED PRIMARY CELL FOR ANALYZING BORON AND CADMIUM IN THORIUM OXIDE USING EMISSION SPECTROGRAPH METHOD - Sahat Simbolon (PTBN - BATAN, 2009)
ABSTRACT AN IMPROVEMENT OF USED PRIMARY CELL GRAPHITE ROD ELECTRODE FOR ANALYZING BORON AND CADMIUM IN THORIUM OXIDE USING EMISSION SPECTROGRAPH METHOD. Analysis of boron and cadmium in synthetic thorium oxide fuel using emission spectrograph method was carried out. Used primary cell graphite rod electrodes (UPCGREs) receiving (chemical and physical) treatment and standard electrodes (Spex) were used as an electrode in the emission spectrograph method. The graphite rod electrodes of used primary cells comprised 50 graphite rod electrodes soaked in water for 2 weeks, 50 graphite rod electrodes soaked in 0.1 N nitric acid for 1 week (chemical treatment), and 50 graphite rod electrodes heated in an oven at 300 °C for 2 hours (physical treatment). Pure thorium oxide was obtained synthetically through thorium nitrate solution extraction using organic solution TBP-kerosene, followed by stripping, drying and calcination. Standards were made from a mixture of synthetic thorium oxide, CdO and H3BO3, and distillation carrier. 100 mg of standards was introduced into the hole of the chemically and physically treated sample-carrying electrodes as well as the standard electrodes (Spex). The operating condition was established using a current of 10 A, an excitation time of 25 seconds, and a gap of 4 mm between electrodes. It was found that when the chemically treated UPCGREs were used as an electrode, the relationship between the concentration and the intensity of boron and cadmium was not in order. Meanwhile, when the physically treated UPCGREs were used as an electrode, the relationship between the concentration and the intensity of boron and cadmium in thorium oxide was linear, therefore it could be used as a calibration curve. It was discovered that the calibration curve of the standard electrodes (Spex) was more sensitive than the calibration curve of the physically treated UPCGREs. However, the calibration curve for boron and cadmium of the standard electrodes (Spex) contained higher background. Therefore, for thorium oxide having low concentrations of boron and cadmium, the use of the physically treated UPCGREs was more favorable than the standard electrodes (Spex). FREE TERMS: used primary cell graphite rod electrode, sample-carrying electrode, boron, cadmium, thorium oxide ABSTRAK PERBAIKAN BATANG ELEKTRODE GRAFIT BATU BATERAI BEKAS UNTUK ANALISIS BORON DAN KADMIUM DALAM TORIUM OKSIDA DENGAN METODE SPEKTROGRAF EMISI. Telah dilakukan analisis boron dan kadmium di dalam bahan bakar nuklir torium oksida sintesis dengan menggunakan metode spektrograf emisi. Batang elektrode grafit batu baterai bekas setelah perlakuan (secara kimia dan fisika) dan elektrode standar (Spex) sebagai pembanding digunakan untuk elektrode pada metode spektrograf emisi. Batang elektrode grafit dari batu baterai yang digunakan mencakup 50 batang elektrode grafit yang direndam dalam air selama 2 minggu, 50 batang elektrode grafit yang direndam dalam 0,1 N asam nitrat selama 1 minggu (secara kimia), dan 50 batang elektrode grafit yang dipanaskan dalam tungku pada suhu 300 °C selama 2 jam (secara fisika). Torium oksida murni disintesis melalui ekstraksi larutan torium nitrat dengan menggunakan larutan organik TBP-kerosin, diikuti stripping, pengeringan dan kalsinasi. Standar dibuat dari campuran torium oksida sintesis dengan CdO dan H3BO3, serta campuran pengemban sulingan. 100 mg standar dimasukkan ke dalam lubang elektrode standar (Spex), maupun elektrode hasil metode kimia dan fisika. Kondisi operasi untuk semua percobaan adalah arus 10 A dengan waktu eksitasi 25 detik dan jarak antar elektrode 4 mm. Hasil percobaan menunjukkan bahwa hubungan antara konsentrasi dan intensitas boron serta kadmium di dalam torium oksida dengan elektrode yang dibuat dengan metode kimia tidak teratur. Sementara itu hubungan antara konsentrasi dan intensitas boron serta kadmium di dalam torium oksida dengan elektrode yang dibuat dengan metode fisika merupakan garis linear yang dapat digunakan sebagai kurva kalibrasi. Adapun kurva kalibrasi boron dan kadmium dengan menggunakan elektrode standar (Spex) masih lebih sensitif dibandingkan dengan elektrode yang diperoleh metode fisika. Akan tetapi latar elektrode standar (Spex) lebih tinggi daripada elektrode yang diperoleh dengan metode fisika. Oleh karena itu untuk torium oksida dengan konsentrasi boron dan kadmium yang rendah lebih baik digunakan elektrode yang diperoleh metode fisika daripada elektrode standar (Spex). KATA KUNCI: batang elektrode grafit batu baterai bekas, elektrode kerja, boron, kadmium, torium oksida